The Irish Sandow school: physical culture competitions in fin-de-siècle Ireland. Issue 3 (3rd July 2019) - Heffernan, Conor
ABSTRACT: Beginning with an examination of Ireland's turn of the century interest in physical culture, this article highlights the case of Eugen Sandow's "Great Competition" and its Irish contestants. Seen as a precursor for today's bodybuilding competitions, Sandow's contest enjoyed submission photographs from hundreds of half-naked men – many of whom were Irish – posing in Greco-Roman pose. In studying this topic, the article addresses two pressing issues. In the first instance, the article examines how and why physical culture competitions became a competitive outlet for Irishmen in the first decade of the twentieth century. Secondly, it argues that these contests were often connected to broader societal ideals surrounding acceptable forms of masculinity. The article thus examines a previously unexplored but nevertheless important part of sporting and athletic behaviour in early twentieth-century Ireland.